Horace's Poetic Journey : A Reading of Odes 1-3 - Porter, David H., 1935-2016 (Book collections on Project MUSE., 1987)
David Porter's approach to Horace's most important lyric collection is through a close sequential reading of the eighty-eight poems in Odes 1-3. Taking into account the way an ancient book was read or recited, this view of the work as a continuously unfolding creation reveals a strong sense of forward movement and of thematic development, at times almost a narrative flow. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.